Reversible regression in early childhood - I. V. Makarov; S. A. Krasnoshchekov (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева, 2021)
Summary. The article (didactic material) addresses the following aspects of the study of reversible regression in early childhood: question history, systematics, regression symptoms, including in childhood autism. The authors analyze the available data, express the opinion that the possibilities of reversible regression therapy in children have not been studied, there are no accurate data on the pathogenesis of these disorders, indicate the need to assess the dynamics of the condition, taking into account the age and sex factors of the child.The authors conclude that reversible regression is a pathological condition developing against a background of relatively favorable child development, in which there is a prolonged decay of previously acquired skills followed by partial or complete recovery. Unlike dementia, which is an irreversible process, regression has the stage of restoring lost functions. In studying the issue, clinical-dynamic analysis of variants of reversible regression of early childhood, an understanding of gender and age differences in the symptoms of the disorder, and prognosis criteria.